Використання штучного інтелекту при навчанні математики молодших школярів - Остапйовська Ірина; Ostapiovska Iryna; Колядич Марія; Koliadych Mariia; Ничипорук Ірина; Nychyporuk Iryna (Видавництво «Код», 2025)
Резюме. У статті виокремлено найбільш перспективні напрями використання штучного інтелекту (ШІ) в початковій школі та конкретизовано їх зміст та наведено приклади їх реалізації із коротким аналізом можливих засобів ШІ. Також обґрунтовано перспективність вивчення культури інформаційної діяльності (КІД) особистості та її медіаграмотності (як компонента КІД).

Abstract. The most promising areas of use of artificial intelligence in primary school were identified as: 1) individualized (personally oriented) learning; 2) automation of processes and administrative management; 3) distance learning (including virtual classrooms); 4) protection and preservation of mental health and psychosocial support; 5) formation and development of «skills of the future»; their content was specified in the article. When individualized (personally oriented) learning in the context of the initial mathematics course has been studying, adaptive educational platforms were defined as a multifunctional, dynamic, reflective educational tool that allows analyzing the individual personal characteristics of the student and, as a result of their analysis and comparison with the planned educational goals, developing the most effective didactic and methodological system for their achievement, as well as making adjustments to it in the event of changes in the structure of the student’s personality or in the content of didactic tasks, and the capabilities of some of adaptive educational platforms were analyzed; the specifics of personalized curricula, the use of virtual tutors and assistants, the features of tracking progress and conducting automated assessments using AI, as well as the gamification of teaching mathematics to younger students, were updated. The content and means of process automation and administrative management were specified. A classification of AI tools in distance learning (including virtual classrooms) was proposed: learning environments, content generation tools, learning environments with educational content generated by artificial intelligence. In this case, the use of AI-generated content in educational environments created by it is envisaged. The capabilities of AI in the direction of protecting and preserving mental health and psychosocial support and the formation and development of «skills of the future» were updated. The prospects of studying the culture of information activity (CIA) of an individual and their media literacy (as a component of CIA) were substantiated too.
Using artificial intelligence in teaching mathematics to young schoolchildren
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: навчання математики молодших школярів; інформаційно-комунікаційні технології; штучний інтелект; медіаграмотність; КІД; використання штучного інтелекту в початковій освіті; використання інформаційно-комунікаційних технологій в початковій освіті